CIVIC CULTURAL DIPLOMACY AS A TOOL FOR PROMOTING UKRAINE’S FOREIGN POLICY GOALS - Holoborodko, Oleh (Public Management and Policy, 2026)
The article explores the role of citizen cultural diplomacy as a tool for promoting Ukraine’s foreign policy goals in the face of constant geopolitical challenges. The transformation of cultural diplomacy from a state-centric model to an inclusive one is examined, where non-state actors play a key role: artists, activists, and public organizations. This paradigm shift reflects the democratization of international interaction, where non-state initiatives complement official narratives. The mechanisms of citizen cultural diplomacy are analyzed, in particular its decentralized, networked nature, rapid adaptability to crisis events, and the use of digital platforms to disseminate cultural content. Examples of successful initiatives that contributed to the formation of a positive image of Ukraine as a democratic nation are given. The impact of citizen diplomacy on Ukraine’s foreign policy is studied (countering Russian propaganda, increasing cultural visibility, attracting international assistance). At the same time, problems are noted (lack of systemic coordination with state institutions, bureaucratic barriers, limited resources in wartime conditions). For the effective integration of citizen diplomacy into national strategies, institutional reform, transparent dialogue between the state and the public, as well as the ethical use of digital technologies to counter disinformation, are necessary. The role of international partnerships and non-governmental actors in the preservation of cultural heritage and the analysis of media discourse is highlighted. It is noted that the lack of high-quality Ukrainian-language media for the diaspora and refugees creates information gaps that reduce the effectiveness of cultural diplomacy. It is established that citizen cultural diplomacy has become a strategic addition to traditional diplomacy, strengthening the “soft power” of Ukraine. However, to realize its potential, systemic changes are needed: institutionalization of coordination mechanisms, support for digital innovations, and strengthening legal and cultural integration. Ukraine’s experience demonstrates that citizen diplomacy can become the basis of international interaction in times of crisis, but requires a balance between the autonomy of the public sector and strategic planning at the state level.